Development, Validity, and Acceptability of Big Book Based on Cebuano Folktales - MALABARBAS, SAIRAH MAE; Mangindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
This study aimed to address the lack of localized instructional materials by developing, validating, and evaluating the acceptability of a Big Book based on Cebuano folktales collected from Polomolok, South Cotabato. The research problem focused on the need for culturally grounded resources that reflect Cebuano heritage and enhance students’ understanding and appreciation of local literature. To address this, the study employed a descriptive research design. Validation was conducted by five (5) experts using frequency and mean, while acceptability was assessed by ten (10) teachers and twenty (20) students and determine significant differences in perceptions regarding the Big Book’s content, objectives, format, and organization. Results indicated that the validators strongly agreed with the quality of the translations and the content of the Big Book. Teachers and students both rated the material as highly acceptable, affirming its effectiveness as a teaching tool. The Cebuano folktales were found to be rich in both material and non-material cultural elements. The study concluded that the Big Book is an effective and appropriate instructional material for promoting regional literature. This research highlights the importance of integrating local culture into educational materials.